Human Rights Theory Rooted in the Writings of Thomas Aquinas (Diametros, 2013)
This essay is an analysis of the theory of human rights based on the writings of Thomas Aquinas, with special reference to the Summa Theologiae. The difference between a jus naturale found in Aquinas and the theory of human rights developed by the sixteenth century scholastic philosophers is articulated. The distinction between objective natural rights—“what is right”—and subjective natural rights—“a right”—is discussed noting that Aquinas held the former position and that later scholastic philosophers beginning with the Salamanca School of the Second Scholasticism developed the latter position. The subjective theory of rights evolved into the modern and contemporary account of individual human rights. The essay ends with an argument suggesting that Aquinas’s theory of objective human rights can serve as the ontological foundation for a robust theory of both positive and negative subjective natural rights.
Keywords: Thomas Aquinas; Francisco Suarez; John Finnis; Henry Veatch; Ralph McInerny; Martha Nussbaum; human nature; natural kind; natural law; objective human right; subjective human right; jus naturale; jus positivum; positive right; negative right